Immune cell infiltration in colonic cancer: correlation between biopsy and surgical specimens. Issue 4 (1st April 2021) - Bordry, N; Germann, M; Foukas, P G; Sempoux, C; Yan, P; Dormond, O; Speiser, D E; Demartines, N; Sauvain, M -O
Abstract : Infiltration of CD3+ and CD8+ T cells in tumour biopsies of patients with colonic cancer correlated positively with CD3+ and CD8+ T cell infiltration in matched tumour surgical specimens. This opens new perspectives in the potential of tumour biopsies for prognosis and treatment decisions.